Al-Muhassinat Al-Badi'iyah in the Book of Love in the Qur'an by Muhammad Saeed Ramadan Al-Bouti - Muis, Muhsin; Faruq, Umarul (Dzil Majaz: Journal of Arabic Literature, 2023)
: Rhetoric is the highest level of linguistic sciences. The lowest level of speech is that which begins with words that indicate their specific meanings, then it gradually reaches the eloquent word and the eloquent phrase. This research reveals the ingenious benefactors and their types contained in the book "Love in the Qur'an according to Muhammad Saeed Ramadan Al-Bouti". The data collection method used is a library method, and the results of the research come as follows: Anaphora in two ten places, division in one place, and interview in one place.